2013
DOI: 10.1001/jamasurg.2013.1221
|View full text |Cite
|
Sign up to set email alerts
|

The Swedish Registry of Gallstone Surgery and Endoscopic Retrograde Cholangiopancreatography (GallRiks)

Abstract: GallRiks is a validated national quality registry for gallstone surgery and ERCP, serving as a base for audit of gallstone disease treatment. It also provides a database for clinical research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(118 citation statements)
references
References 15 publications
4
113
0
1
Order By: Relevance
“…A decrease in open cholecystectomies combined with an increased use of laparoscopic technique in both elective and urgent settings, and lower LOS is also reported in the Swedish Database, GallRiks, were parameters were not predefined [4]. It is therefore difficult to deduct whether the construction of pre-set database goals or the general awareness on a procedure by constructing a database is the determining factor in improving results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A decrease in open cholecystectomies combined with an increased use of laparoscopic technique in both elective and urgent settings, and lower LOS is also reported in the Swedish Database, GallRiks, were parameters were not predefined [4]. It is therefore difficult to deduct whether the construction of pre-set database goals or the general awareness on a procedure by constructing a database is the determining factor in improving results.…”
Section: Discussionmentioning
confidence: 99%
“…For the last decade, increasing attention has been on improving the surgical quality after different procedures by the use of large databases [1][2][3][4][5]. One of these was the Danish Cholecystectomy Database (DCD), which started on January 1, 2006.…”
Section: Introductionmentioning
confidence: 99%
“…In patients from endemic regions undergoing cholecystectomy, 3.5% of gallbladder tissues harbored the bacterium [13] while electron micrographic observation of gallstones retrieved from such individuals demonstrate bacterial biofilm formation on the gallstone surface (Figure 1). Gallstones are present in 5–10% of the human population and gallstone disease is quite widespread [16]. Although identification of non-salmonellae bacteria in gallbladder tissues of cholecystectomy patients is not uncommon [17], gallstones of such patients infected with other Enterobacteriaceae are not similarly covered in a bacterial biofilm [18].…”
Section: The Mechanisms Of Salmonella Persistence In the Gallbladdermentioning
confidence: 99%
“…Thus, they all concluded that prophylactic antibiotics are not needed or warranted for low-risk laparoscopic cholecystectomy. Consequently, a current report documented a trend of not using antibiotic prophylaxis in laparoscopic cholecystectomy [27]. However, most trials in these meta-analyses had a relatively small sample size and were considered to be statistically underpowered for the rare event of infections [28], [29].…”
Section: Introductionmentioning
confidence: 99%